2023
DOI: 10.1186/s13018-023-04116-6
|View full text |Cite
|
Sign up to set email alerts
|

Regenerative peripheral nerve interface reduces the incidence of neuroma in the lower limbs after amputation: a retrospective study based on ultrasound

Zhiyu Lin,
Ping Yu,
Zheng Chen
et al.

Abstract: Background Amputees suffer from symptomatic neuroma and phantom limb pain. Regenerative peripheral nerve interface (RPNI) has recently been regarded as an effective method to prevent neuroma after amputation. However, the verifications of RPNI efficacy are mostly based on subjective evaluation, lacking objective approaches. This study aims to unveil the effect of RPNI on preventing neuroma formation and provide evidence supporting the efficacy of RPNI based on ultrasound. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…31 In retrospective cohort studies that compared patients who underwent standard limb amputation with and without prophylactic RPNI surgery, patients who underwent RPNI surgery consistently had statistically significant better outcomes. [33][34][35] A smaller proportion of RPNI patients developed symptomatic neuromas postoperatively, which was also verified through ultrasound imaging. 33,34 Highresolution ultrasound (US) has been demonstrated in previous studies to be a useful and effective mechanism for diagnosing neuroma.…”
Section: Animal Model Evidencementioning
confidence: 61%
See 4 more Smart Citations
“…31 In retrospective cohort studies that compared patients who underwent standard limb amputation with and without prophylactic RPNI surgery, patients who underwent RPNI surgery consistently had statistically significant better outcomes. [33][34][35] A smaller proportion of RPNI patients developed symptomatic neuromas postoperatively, which was also verified through ultrasound imaging. 33,34 Highresolution ultrasound (US) has been demonstrated in previous studies to be a useful and effective mechanism for diagnosing neuroma.…”
Section: Animal Model Evidencementioning
confidence: 61%
“…[33][34][35] A smaller proportion of RPNI patients developed symptomatic neuromas postoperatively, which was also verified through ultrasound imaging. 33,34 Highresolution ultrasound (US) has been demonstrated in previous studies to be a useful and effective mechanism for diagnosing neuroma. 36,37 On quantified US assessments of the nerve stumps, measurements of cross-sectional area, transverse diameter, and anteroposterior diameter confirmed that control patients developed neuromas while RPNI patients did not.…”
Section: Animal Model Evidencementioning
confidence: 61%
See 3 more Smart Citations